DETECTION AND ANALYSIS OF CYBER-ATTACKS ON IOT NETWORK DEVICES - ADAMU, BASHIR ZAK (Fırat Üniveristesi, 2022)
Adli bilişim ve siber güvenlik alanındaki en önemli zorluklardan birisi de nesnelerin interneti (IoT) ağlarındaki siber saldırıların tespit edilmesidir. İmza tabanlı geleneksel saldırı tespit sistemleri tüm saldırıları tespit edemez. Bu nedenle, özellikle IoT ağlarındaki siber saldırıları hızlı bir şekilde tespit etmek ve ağ trafiğini sınıflandırmak için çeşitli yöntemlerin geliştirilmesi çok önemlidir. Bu tez çalışmasında bir IoT ağı oluşturularak, çeşitli saldırı senaryoları oluşturulmuş ve ağ trafiği kayıt altına alınmıştır. Kayıt altına alınan ağ trafiği çeşitli makine öğrenmesi yaklaşımları ile analiz edilmiş ve yüksek başarım değerlerine ulaşılmıştır.

One of the most pressing concerns in network forensics is the detection of cyber-attacks in the IoT networks and their devices. Traditional intrusion detection systems based on signature rules are unable to detect current attack types. Hence, the need to urgently develop advanced methods for classifying IoT network traffic that can swiftly detect cyber-attacks becomes inevitable. This research aims to develop machine learning algorithms for cyber-attack detection in IoT-based networks, by analyzing the traffic data composed from the network itself. An ideal IoT network was implemented solely for the attack scenarios and generation of a dataset. The self-generated dataset from the IoT network was utilized for the comparison of machine learning algorithms suitable for the classification of attack-to-normal network traffic data. The algorithms are expected to classify the multi-class data into nine classes (normal traffic inclusive).
IoT ağ cihazlarındaki siber saldırıların tespiti ve analizi
Keywords: Bilgisayar Mühendisliği Bilimleri-Bilgisayar ve Kontrol